Pemanfaatan Internet Sebagai New Media Dalam Bidang Politik, Bisnis, Pendidikan Dan Sosial Budaya - Situmorang, James Rianto (Jurnal Administrasi Bisnis, 2012)
New media is a term used to distinguish it with the old media. The lines betweennew media with old media is difficult to determine with certainty because it dependson someoneâs perspective. The Internet can be considered as the beginning of thenew media era because the Internet is very different from the previous media. At thebeginning, the application on the Internet only Website and e-mail. After that camea variety of new applications or new media such as blogs, social networking sites,video sharing sites, online gaming, video conferencing and others. This article limitsthe utilization of the Internet in politics, business, education and sociocultural. Thereason is that these four areas has been utilizing almost all the new media on theInternet.Keywords: new media, internet, utilization, social networking sites, online